Biosynthesis of heterocycles : from the isolation to gene cluster - Diana, Patrizia (Wiley, 2015)
This book describes biosynthetic methods to synthesize heterocycliccompounds, offering a guide for the development of new drugs basedon natural products. The authors explain the role of naturalproducts in chemistry and their formation along with importantanalytical methods and techniques for working withheterocycles. Covers methods and techniques: isotopic labelling, enzymes and mutants, and pathway identification Provides a thorough resource of informationspecifically on heterocyclic natural products and their practicalbiosynthetic relevance Explains the role of natural products in chemistry a.